2020
DOI: 10.3389/fmolb.2020.00090
|View full text |Cite
|
Sign up to set email alerts
|

cis-4-[18F]fluoro-L-proline Molecular Imaging Experimental Liver Fibrosis

Abstract: Molecular Imaging Early-Stage Liver Fibrosis liver collagen expression in the livers of acute steatohepatitis mice (r-value = 0.97, p < 0.001). Conclusion: [ 18 F]fluoro-proline localizes in the liver and correlates with collagenogenesis in acute steatohepatitis with a signal intensity that is sufficiently high to allow imaging with micro-PET/CT. Thus, [ 18 F]fluoro-proline could serve as a PET imaging biomarker for detecting early-stage liver fibrosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 49 publications
1
9
0
Order By: Relevance
“…However, slight differences in TAA compositions were also found between SFBP and HFBP. Proline and hydroxyproline (imino acid) accounted for~23% of the amino acid content of the collagen molecule [36]. In the present study, imino acid residue totaled 183.3 per 1000 total residue in SFBP, which was approximately 1.14 times higher than that of the HFBP (160.6).…”
Section: Proximate and Amino Acid Compositions Of Fbpmentioning
confidence: 44%
“…However, slight differences in TAA compositions were also found between SFBP and HFBP. Proline and hydroxyproline (imino acid) accounted for~23% of the amino acid content of the collagen molecule [36]. In the present study, imino acid residue totaled 183.3 per 1000 total residue in SFBP, which was approximately 1.14 times higher than that of the HFBP (160.6).…”
Section: Proximate and Amino Acid Compositions Of Fbpmentioning
confidence: 44%
“…In another study, [ 18 F]MAGL-4-11 demonstrated reduced PET signals in the early stages of fibrosis and further significantly decrease with disease progression compared with control mice (14). Previously, we identified a [18F]proline that could serve as a PET imaging biomarker for detecting early-stage liver fibrosis in an LPS-induced mice model (15). That study was not powered to stage liver fibrosis as the animals were only imaged at an early-stage time point.…”
Section: Introductionmentioning
confidence: 95%
“…Liver histology is the classic diagnostic method to estimate the progression of liver fibrosis which relied on professional pathologists, because it is time-consuming, invasive, difficult to operate, and expensive, and poses a variety of complications, the application of liver biopsy is limited in clinic ( McGill et al, 1990 ). Several noninvasive methods have been reported that could be used in evaluating the severity of liver fibrosis ( Cao et al, 2020 ; Loomba and Adams, 2020 ). One of the most common noninvasive scoring systems is the aspartate aminotransferase-to-platelet ratio index (APRI) and the other is fibrosis index based on the four factors (FIB-4), both of them have been indicated to predict severe liver fibrosis or liver cirrhosis ( Wai et al, 2003 ; Vallet-Pichard et al, 2007 ).…”
Section: Introductionmentioning
confidence: 99%